Why Wound Healing in the Oral Cavity Occurs Faster than in the Skin - Orliando Roeslan, Moehamad; Wulansari, Selviana; Hanum Tazkia, Rahardianty (Fakultas Kedokteran Gigi Universitas Trisakti, 2025)
Oral wound healing is faster and more effective than skin wound healing, a process that is fueled by a complex interplay of cellular, molecular, and environmental processes. This review delves into the unique mechanisms of the enhanced regenerative ability of oral tissues. Oral fibroblasts have increased proliferative activity, specific adhesion profiles, and distinct signalling pathways that promote scarless healing. The oral cavity's immune microenvironment is that of blunted inflammation and repair-conducive cytokine profile, with predominance of M2 macrophage response and increased generation of anti-inflammatory mediators. Oral epithelial cells also allow for rapid healing of wounds through enhanced migration and proliferation, regulated by a salivary humid environment. Saliva itself plays a crucial role in that it acts as a reservoir of growth factors, antimicrobial peptides, and cytokines that collectively facilitate epithelialization, angiogenesis, and immune modulation. Skin wounds, however, are generally exposed to chronic inflammation, drier environment, and higher scarring potential. Understanding these fundamental differences not only enhances our knowledge of tissue-specific healing but also opens avenues for developing targeted therapeutic strategies that mimic oral wound healing mechanisms to improve dermal repair outcomes.